Modeling and analysis of thermal runaway in Li-ion cell. (September 2019) - An, Z.; Shah, K.; Jia, L.; Ma, Y.
Highlights: An analytical model to predict thermal runaway of lithium-ion cells. Validation of the model through comparison with experiments and other models. Application of the model for the design to prevent thermal runaway. Demonstration of an effective tool for thermal runaway analysis and prevention. Abstract: Thermal runaway is the top safety concern for Li-ion electrochemical energy storage systems. There are multiple abuse conditions that may cause thermal runaway in Li-ion cells. Although thermal runaway has been extensively studied, the runaway mechanisms due to external short circuit and ultra-high discharge rates (>10C) are relatively less studied. In the present work, an analytical thermal runaway model is developed to predict thermal runaway in prismatic and pouch Li-ion cells due to either external short circuit or ultra-high discharge rates. The heat generation data corresponding to the ultra-high discharge rates considered in the thermal runaway model have been obtained separately using an electrochemical-thermal coupled model. The analytical thermal runaway model is validated against experiments as well as COMSOL, a finite element-based commericial solver. Using the analytical model, the effects of key parameters on cell safety have been analyzed. Finally, the analytical model has been used to evaluate effectiveness of a thermal runaway prevention strategy based on boiling in minichannels of a water-cooled minichannel based battery thermal management system.